2008
DOI: 10.1007/s00203-008-0427-x
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK as a signal transduction component of heavy metals stress in Euglena gracilis

Abstract: Living organisms are subject to stress, and among these stressors, heavy metals exposure triggers accumulation of sulfur metabolites. Among these metabolites, glutathione and phytochelatins are found in several organisms, such as Euglena gracilis. Pre-exposing E. gracilis to low concentrations of Hg2+ generates a population with resistance to even 0.2 mM Cd2+, and this resistance relies partly on phytochelatins. p38 MAPK is stimulated by stress and is involved in apoptotic as well as survival mechanisms. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…According to Rios-Barrera et al (2008), heavy metals such as cadmium and mercury exhibited p38 MAPK activity that mediates redox stress of the MAPKK signal pathways in Euglena gracilis. P38 MAPK pathways was discovered to be associated with apoptosis, stress responses and immunity (Johnson & Lapadat 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Rios-Barrera et al (2008), heavy metals such as cadmium and mercury exhibited p38 MAPK activity that mediates redox stress of the MAPKK signal pathways in Euglena gracilis. P38 MAPK pathways was discovered to be associated with apoptosis, stress responses and immunity (Johnson & Lapadat 2002).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, p38 MAPK acts as a signal transduction component of heavy metals stress that mediates redox stress component of signal induction pathway when exposed to heavy metals (Rios-Barrera et al 2008). A review by Ventura-Lima et al (2011), reported that arsenic in aquaporins could affect signalling pathways by activating proteins such as ERK2, p38 and JNK as demonstrated in mammals.…”
Section: Introductionmentioning
confidence: 99%